A qualitative study on barriers and facilitators of COVID-19 vaccination during pregnancy among pregnant women in Malaysia - Muhammad Hafiz Mohamed Pauzi; Azidah Abdul Kadir; Rosediani Muhamad; Zainab Mat Yudin (PLoS ONE, 2025)
Background COVID-19 vaccination is crucial for pregnant women to protect against severe complications during pregnancy. However, vaccine hesitancy and refusal can affect acceptance rates among this vulnerable group, posing risks to both maternal and fetal health. This research was conducted to explore the barriers and facilitators influencing COVID-19 vaccination among Malaysian pregnant women. Methods This qualitative study adopted a hermeneutic phenomenological design. Nineteen pregnant women receiving antenatal care at three clinics in Kelantan between February 2024 and June 2024 were purposively selected to participate in in-depth interviews. The interviews were audio-recorded, transcribed verbatim, and analyzed using NVivo software alongside manual coding. Thematic analysis, incorporating both inductive and deductive approaches, was conducted to identify key themes. Results Most pregnant women expressed hesitancy toward COVID-19 vaccination during pregnancy due to various concerns. Our findings identified four key themes as barriers to vaccination: (i) Fear of side effects, (ii) Negative social influences, (iii) Perception of returning to normalcy, and (iv) Vaccine scepticism and prejudice. Conversely, three themes emerged as facilitators of vaccine acceptance: (i) Concerns about the effects of COVID-19 infection, (ii) Trust in the vaccine, and (iii) Personal and shared vaccination experiences. Conclusion This study identified key factors influencing COVID-19 vaccine hesitancy. These findings highlight the importance of addressing both personal and social dimensions of vaccine hesitancy. Public health interventions should focus on building trust, countering misinformation, and leveraging positive community experiences to encourage vaccine uptake, particularly in populations where hesitancy remains a concern.